2015
DOI: 10.19030/jier.v11i4.9459
|View full text |Cite
|
Sign up to set email alerts
|

The Effect Of Blended Learning Approach On Fifth Grade Students’ Academic Achievement In My Beautiful Language Textbook And The Development Of Their Verbal Creative Thinking In Saudi Arabia

Abstract: This study aims at investigating the effect of Blended Learning approach compared to the traditional learning approach on fifth grade students’ achievement in My Beautiful Language Textbook and the development of their verbal creative thinking. The study consisted of 49 students among which 25 are males in the Experimental Group and 24 females in the Control Group. The study found a statistical significant difference (α ≤ 0.05) between the mean scores of the two study groups in achievement posttest and verbal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In line with the findings of this study, previous researchers envisioned that new technology such as computer-assisted instruction should be used in the teaching of abstract concept in mathematics (Ahmad et al, 2008; Awodeyi et al, 2014; Bhatti, 2013). The findings of this study is also in agreement with many previous studies such as (Al-Ghassani et al, 2015; Al-Madani, 2015; Awodeyi et al, 2014; Ceylan & Kesici, 2017; Delaney et al, 2010; Fakhir, 2015; Lin et al, 2017; Siew-Eng et al, 2010; Syarif & Sofyan, 2012; Viz & Kaur, 2017; Yilmaz & Oghan, 2010) all of which reported blended learning as a good approach with a potential of improving students achievement and instructional delivery in mathematics courses as well as understanding of concepts in the subject matter (Akgündüz & Akınoğlu, 2017; Awodeyi et al, 2014; Balasubramaniam et al, 2018; Lin et al, 2017; Rozeboom, 2017). It is also in line with the findings of Almasaeid (2014) who found improved science achievement and with the findings of Olelewe and Agomuo (2016), who found an improved achievement in programing language.…”
Section: Effect On Mathematics Achievementsupporting
confidence: 94%
“…In line with the findings of this study, previous researchers envisioned that new technology such as computer-assisted instruction should be used in the teaching of abstract concept in mathematics (Ahmad et al, 2008; Awodeyi et al, 2014; Bhatti, 2013). The findings of this study is also in agreement with many previous studies such as (Al-Ghassani et al, 2015; Al-Madani, 2015; Awodeyi et al, 2014; Ceylan & Kesici, 2017; Delaney et al, 2010; Fakhir, 2015; Lin et al, 2017; Siew-Eng et al, 2010; Syarif & Sofyan, 2012; Viz & Kaur, 2017; Yilmaz & Oghan, 2010) all of which reported blended learning as a good approach with a potential of improving students achievement and instructional delivery in mathematics courses as well as understanding of concepts in the subject matter (Akgündüz & Akınoğlu, 2017; Awodeyi et al, 2014; Balasubramaniam et al, 2018; Lin et al, 2017; Rozeboom, 2017). It is also in line with the findings of Almasaeid (2014) who found improved science achievement and with the findings of Olelewe and Agomuo (2016), who found an improved achievement in programing language.…”
Section: Effect On Mathematics Achievementsupporting
confidence: 94%
“…The study concluded that there is a statistically significant difference (α ≤ 0.05) between the mean scores of the two groups in the achievement post-test and verbal creative thinking post application test. The study also concluded that the experiment group with which the blended approach was used outperformed the control group that was taught using traditional methods in both tests [21]. Similarly, Yassin investigated the use of blended learning for teaching Arabic in an adult class of Arabic as a foreign language in the Singaporean context.…”
Section: Blended Learning In Afl and Aspmentioning
confidence: 96%
“…Moreover, the results of the literature analysis and the problems with current learning methods indicate that there is still a gap in the learning approach that needs to be explored. Overall, many studies have explored the perceptions of blended learning (Bauk, 2015;Bower et al, 2015), advantages of blended learning (Biddix et al, 2015;Güzer & Caner, 2014;Shams, 2013) and effectiveness of blended learning (Al-Madani, 2015). There are several studies that discuss blended learning and its relevance to achievement in various aspects.…”
Section: Blended Learningmentioning
confidence: 99%
“…Students give positive feedback on math learning using Moodle. Al Madani (2015) found that the use of blended learning for language courses can improve student achievement and encourage critical thinking compared to traditional approaches.…”
Section: Mastery Of Basics Photographymentioning
confidence: 99%